Probiotics to prevent acute respiratory infections in pediatric and adult populations - Espinosa, Alisson Camila Valladares; Balanzategui, Camila Brito; Velasco, Albert Isaac Grijalva; Márquez, Pierina Inés Cantos; Cadena, Marilyn Paola León; Jácome, Dario David Chicaiza; Rodríguez, Carlos A. Chango; Pineda, Galo D. Moreno (International Journal of Research in Medical Sciences, 2025)
Respiratory tract diseases are among the most common infections of childhood and adolescence. Probiotics in recent years have been presented as a promise and prophylactic and curative alternative for various digestive, mental and respiratory pathologies. This is attributed to the great influence that the intestinal microbiota exerts on the immune system. Multiple studies indicate that an impact on the microbiota due to external or internal factors generates an alteration of the immune system. Among the uses that currently exist, they are used for the prevention and treatment of respiratory diseases in children, adolescents and adults. From the studies analysed, it is observed that Lactobacillus casei shows better results in the prevention of upper respiratory diseases than the rest of the probiotics in combination or alone, however the necessary administration time is unknown.